Labor mobility in a monetary union - Daniela Hauser; Martin Seneca (Bank of Canada, 2019)
The optimal currency literature has stressed the importance of labor mobility as a precondition for the success of monetary unions. But only a few studies formally link labor mobility to macroeconomic adjustment and policy. In this paper, we study macroeconomic dynamics and optimal monetary policy in an economy with cyclical labor flows across two distinct regions that share trade links and a common monetary framework. In our New Keynesian dynamic, stochastic, general-equilibrium model calibrated to the United States, migration flows are driven by fluctuations in the relative labor market performance across the monetary union. While labor mobility can be an additional channel for cross-regional spillovers as well as a regional shock absorber, we find that a mobile labor force closes the efficiency gaps in the labor market and thus lessens the trade-off between inflation and labor market stabilization. As migration flows are generally inefficient, however, regionspecific disturbances introduce additional trade-offs with regional labor market conditions. Putting some weight on stabilizing fluctuations in the labor market enhances welfare when monetary policy follows a simple rule.
Keywords: E32; E52; F45; 330; Business fluctuations and cycles; Labour markets; Economic models; Monetary policy framework; Regional economic developments